Association of Low Leptin with Poor 3-Month Prognosis in Ischemic Stroke Patients with Type 2 Diabetes - Zou Y (Dove Medical Press, 2020)
Yi Zou,1 Ling Hu,1 Wenjun Zou,2 Honglin Li3 1Department of Endocrinology, The Third Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 2General Surgery, Nanchang Third Hospital, Nanchang, People’s Republic of China; 3Department of Biochemistry, Medical College of Georgia, Augusta, GA, USACorrespondence: Ling HuDepartment of Endocrinology, The Third Affiliated Hospital of Nanchang University, No. 128 Xiangshan North Road, Nanchang 330000, Jiangxi Province, People’s Republic of ChinaTel +86 791-88862350Email hul@medmail.com.cnBackground: Leptin, an adipokine, has effects on the cardiovascular system with both protective and harmful role. This study aimed to assess the relationship between leptin and 3-month prognosis in ischemic stroke patients with type 2 diabetes.Patients and Methods: As a prospective single-center observational study, we collected consecutive first-ever acute ischemia stroke with type 2 diabetes mellitus from February 2019 to February 2020. Serum samples were obtained at admission, and leptin serum levels were tested by the ELISA method. Logistic regression models were used to assess leptin’s prognostic value to predict the functional outcome and mortality within three months.Results: Finally, two hundred and eleven patients were included, and the mean leptin serum level was 16.8 (SD. 6.9) ng/mL. At admission, 53.6% of those included patients (N=113) were defined as severe stroke (NIH Stroke Scale [NIHSS]> 5). In multivariable models adjusted for other factors, leptin levels< 11.6ng/mL (lowest quartile, Q1) related to severe stroke and the risk increased 175% (odds ratios [OR] =2.75; 95% confidence interval [CI]=2.13– 3.38; P=0.002). Serum leptin levels on admission in patients with poor outcomes and nonsurvivors were significantly reduced (P< 0.001 and P< 0.001). Leptin levels < 11.6ng/mL (lowest quartile, Q1) related to a higher risk of poor functional impairment (OR=5.13; 95% CI =3.25– 6.86; P< 0.001) and mortality (OR=3.19; 95% CI =2.03– 4.25; P< 0.001).Conclusion: The data shows that leptin serum level is a useful prognostic biomarker in ischemic stroke patients with type 2 diabetes, and this relationship is negative.Keywords: leptin, adipokine, ischemic stroke, type 2 diabetes, prognosis